Track‐Etched Nanopore/Membrane: From Fundamental to Applications. Issue 9 (8th July 2020) - Ma, Tianji; Janot, Jean‐Marc; Balme, Sébastien
Abstract: Biomimetic and bio‐inspired membranes draw great attention and generate extensive efforts to solve environmental, health, and energy issues. In this field, track‐etched membranes present the advantage to be tuned from a single pore to a large‐scale multipore membrane. On one hand, from the large‐scale membrane to a single nanopore, the research becomes more fundamental, meticulous, and quantitative to describe concrete processes inside confined spaces. This allows understanding the role of the surface phenomena and nanoscale effects. On the other hand, working from a single pore to a multipore membrane allows perfect control of the membrane properties. This ensures a promising ability for upscale from the lab findings to applications. In this review, a global insight on the track‐etched nanopore/membrane is taken through presentation of fabrication and functionalization methods, transport properties, and the related applications. By functionalization, track‐etched nanopores can be used to understand ion transport under confined spaces with high aspect ratio, to analyze single molecules, to design stimuli‐responsive membranes, and to generate energy from salinity gradient and light. Abstract : This review gives an overview on the track‐etched nanopore/membrane from their design to their applications. The different steps of fabrication and the strategy of functionalization are discussed. Then, the ionic transport properties under confined space are reminded. The application of the track‐etched nanopore/membrane to stimuli‐responsive ion channels, ion gate, molecule sensing, and energy production are shown and discussed.